2003
DOI: 10.1114/1.1535412
|View full text |Cite
|
Sign up to set email alerts
|

Volume Currents in Forward and Inverse Magnetoencephalographic Simulations Using Realistic Head Models

Abstract: Volume currents are important for the accurate calculation of magnetoencephalographic (MEG) forward or inverse simulations in realistic head models. We verify the accuracy of our finite element method implementation for MEG simulations by comparing its results for spheres containing dipoles to those obtained from the analytic solution. We then use this finite element method to show that, in an inhomogeneous, nonspherical realistic head model, the magnetic field normal to the MEG detector due to volume currents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 11 publications
4
25
0
Order By: Relevance
“…The volume current 0018-9464/$25.00 © 2009 IEEE is attributed to the effect of the macroscopic electric field on charge carriers [4]. It has been shown that for a realistic brain model with inhomogeneous conductivity distribution, the magnetic field from this volume current can be comparable with that from the primary current source (e.g., dipole) [5]. Thus, the total current density becomes (5) where is the electric scalar potential.…”
Section: A Mathematical Modelmentioning
confidence: 88%
“…The volume current 0018-9464/$25.00 © 2009 IEEE is attributed to the effect of the macroscopic electric field on charge carriers [4]. It has been shown that for a realistic brain model with inhomogeneous conductivity distribution, the magnetic field from this volume current can be comparable with that from the primary current source (e.g., dipole) [5]. Thus, the total current density becomes (5) where is the electric scalar potential.…”
Section: A Mathematical Modelmentioning
confidence: 88%
“…In case of Section 4 below, conductivity of the brain material plays a major role and, therefore has to be carefully considered [13]. Due to high complexity and anisotropy level, each element has to have its own material properties which leads to a complicated structure of matrix for material properties.…”
Section: Number Of Anisotropic Element Properties In the Model Pmentioning
confidence: 99%
“…Indeed, dipoles that were "deep" in the head were generally more influenced by changes in conductivity values, whether they were changes in the gray matter or white matter, than were more superficially located dipoles. The smaller localization errors found with superficial dipoles would be expected based on equation (1), which implies that superficially located dipoles should produce magnetic fields with relatively low contributions from volume currents or influence from conductivity.…”
Section: Discussionmentioning
confidence: 68%
“…The finite element realistic head model was created from 256 volume magnetic resonance image (MRI) slices and consisted of 72,745 nodes, 406,493 tetrahedral elements, and 61 magnetic field detectors placed over the head [1]. The model consisted of five conductivity values: scalp (σ=1.0 S/m), skull (σ=0.05 S/m), cerebrospinal fluid (CSF) (σ=4.62 S/m), gray matter (σ=1.0 S/m), and white matter (σ=0.43 S/m) [2]; these conductivity values were considered the baseline conductivities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation